Energy-aware compilation and hardware design for VLIW embedded systems. (3rd December 2007) - Ayala, Jose L.; Lopez-Vallejo, Marisa; Atienza, David; Raghavan, Praveen; Catthoor, Francky; Verkest, Diederik
Tomorrow's embedded devices need to run multimedia applications demanding high computational power with low energy consumption constraints. In this context, the register file is a key source of power consumption and its inappropriate design and management severely affects system power. In this paper, we present a new approach to reduce the energy of shared register files in forthcoming embedded VLIW processors running real-life applications up to 60% without performance penalty. This approach relies on limited hardware extensions and a compiler-based energy-aware register assignment algorithm to deactivate at run-time parts of the register file (i.e., sub-banks) in an independent way.